Factors influencing college teachers’ adoption of live online teaching: a conditional process model of technology acceptance, user satisfaction and privacy concerns - Xiao, Wan; Wang, Meiqin; Mo, Jiaqian (Frontiers in Psychology, 2024)
Purpose: In recent times, live online teaching has emerged as a prominent trend in online education.However, teachers are confronted with the challenge of not only acquainting themselves with the associated technologies but also effectively integrating them into their teaching practices. This dual challenge exerts pressure on teachers to adopt live online teaching. This study aims to explore the factors and mechanisms influencing teachers' attitudes and continuance intention towards live online teaching. It covers both intrinsic and extrinsic motivations, as well as both enabling and inhibiting factors, thus providing valuable suggestions for encouraging teachers to engage in live online teaching actively.Method: This study proposed a conceptual model based on the Technology Acceptance Model, Uses and Gratifications Theory, and Communication Privacy Management Theory. A simple random sampling method was employed to recruit participants from a university in eastern China. With 224 college teachers participating in the study, various analyses, including descriptive analysis, regression analysis, and simple slope analysis, were conducted to explore the factors and mechanisms influencing college teachers' adoption of live online teaching.Results: The study revealed the following key findings: a) perceived easy of use had a positive impact on perceived usefulness and user satisfaction; b) perceived usefulness had a positive effect on user satisfaction; c) both perceived usefulness and user satisfaction positively influenced teachers' adoption of live online teaching; d) perceived easy of use did not directly affect teachers' adoption of live online teaching; e) privacy concerns exhibited a moderated effect on the relationship between perceived easy of use and perceived usefulness, as well as the relationship between perceived easy of use and user satisfaction.The study reveals a conditional process model elucidating teachers' adoption of live online learning. The model incorporates perceived ease of use as a predictor, perceived usefulness and user satisfaction as two mediators, and private concerns as a moderator. The findings suggest that stakeholders should collaborate closely to enhance the design and development of the live online teaching platforms. Additionally, efforts should be made to support and improve teachers' information literacy, fostering their enthusiasm and facilitating their professional development in live online teaching practice.